(untitled) (Research, Society and Development, 2022)
The development, production and marketing of bras suitable for different morphological types of women, have been a challenge not only of the production sector (which should offer bras with usability) but also (and especially) the Research and Development (R&D) sector of the fashion industry, in Brazil and worldwide. This situation has been reflected in frustration and discomfort by the users of this important component of the current fashion. The objective of this study was to explore, analyze and discuss the scientific articles about the perception of bra wearing, by adult women, from a systematized literature review (SLR). The method for the elaboration of the question was the PICO and the process checklist was the PRISMA. Data were collected in the platforms Capes, Scielo and Scopus; and 136 articles were identified that, when applying the inclusion/exclusion and eligibility criteria, resulted in 13 eligible articles. These articles were analyzed quantitatively, with numerical understanding, and qualitatively, in which the contents addressed were critically analyzed. In this sense, the present study points out that different studies were identified and discussed that reinforce the hypothesis related to the problems of interaction product (bra) and user (women); and that there is still a lack of applied approaches aimed at the search for knowledge that demonstrate the solution of these problems related to the bra.